The role of university council structures, systems and cultures in bringing about effective university governance in a comprehensive university - Omal, Felix (My University, 2016)
This study provides an analysis of the role of university councils in Historically Disadvantaged Institutions (HDIs) in bringing about effective governance. It adopts a case study approach of a single institution which became a comprehensive university following the Higher Education post-1994 transformation agenda in South Africa. The study explores the role of systems, structures and cultures of university councils in promoting effective university governance. It arises from widespread concern about poor university governance which has resulted in no less 10 institutions being placed under administration in the post-1994 democratic era. This study used a range of theoretical and methodological approaches. The theoretical approaches involved the use of the following concepts as an organizing framework: “structures of university councils”, “systems of university councils”, “cultures of university councils” and “empowered individuals” or “groups of individuals”. The methodological approaches involved data collection within a sequential-exploratory mixed methods research interpretive paradigm and the positivist research paradigms. The process of data collection involved; the use of institutional documents, interviews with 19 different members of the university council and study surveys with available 17 university teaching staff, 48 university non-teaching staff and 255 university students. The process of data analysis involved the use of content analysis, descriptive and inferential statistics. The results of this study show that the institutional structures of the university council are business oriented in organization although strongly characterised by institutional stakeholder relationships. This has led to effective governance practices being tied around forms of stakeholder propositions such as increased sectoral deployment of constituency cadres to champion particular stakeholder interest at the university council. The results of this study indicate this has led to conditions and instances where the systemic due processes of the university council are prone to stakeholder control. This is due to instances of unpreparedness for general council and committee meetings an outcome of sectoral deployment of individuals who have little if not no idea of the due processes at the systems level of the university council and reliance on informal stakeholder constituent networks as a mode of trust governance. This has led to less sovereignty for critical autonomy to check on strong stakeholder configurations at the university council leading to reproduction of dormant stakeholder interests. At the cultural level of the university council the results of this study show that to respond to these conditions the university council has become stakeholder managerial driven. The university council cultural governance actions as governance role practices are strongly stakeholder enthused. The implication of governance stance has caused contestations between the less empowered institutional stakeholders represented at the university council and the university council over practices that are seen as perpetuating marginalisation of the less empowered institutional stakeholders represented at the university council. As a result it has led to adoption of partisan modes of stakeholder institutional governance practices like caucuses, stakeholder deployment, protest, and unionisation. This thesis as a recommendation makes a case through an emerging model of university governance known as the structural-systemic-cultural university governance model. This model suggests that for the university council to be able to provide effective university governance in such comprehensive institutional contexts, it should take in consideration the following: At the structural level, governance should be characterised by practices that recognise the place of the university council in decision-making process in the university institution, governance capacity-building, networked committee regimes, effective representation and utilisation of delegated institutional governance spaces. At the systemic level, governance should be characterised by practices that value stakeholder contribution, support well-informed of committees of council, well informed constituents, accountability and compliance engagement as part of the core due processes of the university council. At the cultural level, governance should be characterised by practices that appreciate accessible governance spaces, accommodativeness, negotiated positions and shared accountabilities as part of the primary bases that characterise institutional culture of the university governing council. Key words: university council, structures, systems, cultures, effective university governance, comprehensive university
A thesis submitted to the School of Education, Faculty of the Humanities, of the University of the Witwatersrand in the fulfilment of the requirements for the degree of Doctor of Philosophy in Education JOHANNESBURG NOVEMBER 2015
Keywords: University council; Structures; Systems; Cultures; Effective university governance